"IMPROVING STUDENTS' WRITING ABILITY THROUGH COMPLETION SHORT STORY OF SECOND YEAR HIGH SCHOOL AT UNAI LABSCHOOL" - Nelson B Panjaitan; Okamura Silitonga; Mian Silitonga (Journal of Language Pedagogy, 2011)
This research is entitled "Improving Students Writing Ability Through Completion ShortStory Of Second Year Junior High School at Unai Labschool".This research was administered to answer the question "does completion short storysignificantly improve writing capability of second year junior high School at Unai LabSchool?" The data were collected through pre-test and post test, administered to 15 studentsand the data was analyzed by using T-test.The researcher gave the pre-test and post-test through incomplete short story form to collectthe data. And the data is analyzed by using T-Test in SPSS (Statistical for service Solution)The results showed that the participants' of writing achievement was improved throughCompletion Short Story Strategy and the score gained by participants showed that there was asignificant effect of Completion Short Story Strategy. It is strong enough to improve thestudents' writing ability. The achievements showed that the mean difference between pre-testand post-test is 18 the t w„aed= -4.306 < t pie= -2.048 with significance level in 0.05. Standarderror mean of pre-test is 3.73078 and post-test 2.02477.The researcher hopes that the finding of present study could give some contribution to theimprovement on the teaching writing especially for junior high school at Unai.